(untitled) (Raparin Journal of Humanities (RJH), 2023)
Undoubtedly, Characters are of great significance in novels cannot be written without them. Characters are comprised of a numbers of dimensions which play an important role in making the characters. This thesis attempts to analyze the dimensions of making the characters in the novel using a descriptive analysis method. Our research consists of two chapters. The first part entitled” theorized the concepts of the research”, an account is given regarding the main terms of the study including “dimensions, character, the process of making character, and the types of character in novels”. The second part entitled “the dimensions of character pedestal in the novel "Nights of Adam" by Bayan Salman”.